Placements and work-based learning in education studies an introduction for students - Hordern, Jim; Simon, Catherine (Foundations of education studies series., 2017)
"Written specifically for education studies students, this accessible text offers a clear introduction to placements and work-based learning, providing an insight into work in schools and education settings. Including case studies to illustrate the diversity of placements and workplace opportunities, it explores the theory and practice of working in educational contexts and supports students as they develop the skills and aptitudes that enhance their employability."--Provided by publisher.